Rectus Abdominis Myofascial Flap for Vaginal Reconstruction After Pelvic Exenteration. Issue 5 (November 2018) - Cortinovis, Umberto; Sala, Laura; Bonomi, Stefano; Gallino, Gianfrancesco; Belli, Filiberto; Ditto, Antonino; Martinelli, Fabio; Bogani, Giorgio; Leone Roberti Maggiore, Umberto; Raspagliesi, Francesco
Abstract : Background: Several techniques for vaginal reconstruction after pelvic exenteration such as myocutaneous and myoperitoneal flaps are available. However, the use of a myofascial flap has not been previously described. Thus, the objective of this article is to present our experience of vaginal reconstruction with rectus abdominis myofascial (RAMF) flap. Methods: Between May 2008 and March 2017, 16 patients underwent anterior, posterior, or total pelvic exenteration with RAMF flap vaginal reconstruction. Patient records were systematically reviewed; demographic, clinic and pathologic, operative details, flap-related and non–flap-related complications, and risk factors for wound healing are reported. Quality of life and sexual function were also investigated. Results: Eleven (68.8%) of 16 patients died during the follow-up (29.1 ± 25 months), whereas 5 (31.3%) are still alive. Early complications were reported in 7 patients (43.8%), with 2 (12.5%) flap-related and 5 (31.3%) non–flap-related complications. Similarly, late complications were reported in 5 patients (31.3%), with 2 (12.5%) flap-related and 3 (18.8%) non–flap-related complications. Quality of life measured by SF-36 (Survey Short Form 36) significantly improved at 12-month follow-up in comparison with baseline (physical component summary 31.5 ± 4.8 vs 26.8 ± 2.9; P = 0.027; mental component summary 29.5 ± 6.0 vs 25.9 ± 2.0; P = 0.042). Conclusions: This study demonstrates for the first time that RAMF flap vaginal reconstruction after pelvic exenteration is an efficacious and safe technique. Furthermore, it is associated with a significant improvement of quality of life and sexual function in those women who had sexual intercourse before surgery.